Experience of Endoscopic Transcapsular Axillary Nerve Decompression - E. A. Belyak; S. A. Asratyan; M. F. Lazko; F. L. Lazko; D. L. Paskhin; A. P. Prizov; D. S. Smirnov (Неотложная медицинская помощь)
INTRODUCTION Posttraumatic axillary nerve neuropathy is a widely spread pathology, more often seen after shoulder joint trauma. It can also occur as a complication after orthopaedic surgeries, for example, after Latarjet procedure for shoulder stabilization. The technique of open axillary nerve decompression is very popular but has a number of disadvantages: large trauma of soft tissue, severe bleeding, high rate of complications, poor cosmetic effect. Endoscopic surgical technique of decompression is an effective, less traumatic alternative to open procedures.AIM To improve the outcomes of treatment of patients with axillary nerve neuropathy.MATERIAL AND METHODS We present the outcomes of endoscopic transcapsular axillary nerve decompression in 5 patients with a clinical picture of neuropathic pain syndrome, hypoesthesia in the deltoid area, hypotrophy of the deltoid muscle, who were operated from 2018 to 2021. The mean age of the patients was 44.4±14.9. An original surgical technique of decompression, which included arthroscopy of the shoulder joint with diagnostic and treatment components and transcapsular endoscopic axillary nerve decompression in the beach-chair position, was developed and applied to all the patients. Statistical analysis was performed using the MannWhitney U test.RESULTS According to VAS-scale, the severity of pain syndrome before the surgery was 6±4.6 points, 6 months after surgery it decreased to 1.4±0.5 points (p<0.05). According to DASH scale, the function of the of shoulder joint before surgery was 77,6±6,9 points, 6 months after surgery it increased to 12±5,2 points (p<0.05). According to BMRC scale (M0–M5), strength of the deltoid muscle before surgery was 2±0,4 points, after surgery it increased to 4,4±0,5 points (p<0.05). Range of motion in the shoulder joint before surgery was as follows: flexion 107±45,6°, extension 102±49°, external rotation 22±13,6°; 6 months after surgery: flexion 154±25,6°, extension 156±22,4°, external rotation 50±8° (p<0,05). The thickness of the middle portion of the deltoid muscle according to ultrasound examination before the surgery was 7.2±1.04 mm, after surgery 11.8±1.44 mm (p<0.05). All the patients (100%) during long follow-up noticed complete relief of pain and regression of neurological symptoms.CONCLUSION The achieved results allow us to characterize the method of endoscopic transcapsular decompression as a reproducible, minimally invasive and highly effective technique providing pain relief to patients, curing neurological and intraarticular pathology, thus promoting early restoration of the upper limb function in the treated group of patients.